Pembuatan Pewarna Alam Dari Kulit Bawang Bombay (Allium Cepa L) Pada Kain Sutra Dan Katun - Rizki Lestari; Aditya Dimas Wahyu Sasongko; Maghfiroh Maghfiroh; Zahir Widadi; Yovita Christy; Tryas Intan Pandini (KOLONI, 2026)
Natural dyes for fabrics are often derived from plants; however, it is important to consider the sustainability of the plant ecosystem when using natural dyes. We must ensure that the use of natural dyes to reduce environmental pollution does not end up damaging the plant ecosystem. One alternative for using natural dyes in batik that utilizes local natural resources is the production of natural dyes from onion skins. Onions can serve as an alternative natural dye for batik fabric. In addition to being an alternative for natural dyes in batik, this method can also function as a strategy for household waste management, offering varied and environmentally friendly batik dyeing. Using an experimental method with quantitative analysis, three mordanting stages—pre-mordantting, simultaneous mordanting, and post-mordanting—were applied, along with the nglorod process, consistent with traditional batik production methods. Onion skins were processed to serve as a dye for silk and cotton fabrics, with tests conducted for colorfastness to washing, perspiration, and rubbing. The research results showed that the color extracted from onion skins was reddish-yellow; on silk fabric, the color was darker compared to cotton fabric. After the nglorod process, the colorfastness of cotton fabric tended to be higher than that of silk, while silk was more stable and even more intense. Further testing was conducted on colorfastness to washing, rubbing, and perspiration. Laboratory test results showed that silk fabric performed better.